Cognitive Reserve, Leisure Activity, and Neuropsychological Profile in the Early Stage of Cognitive Decline - Lee, Sook Young; Kang, Jae Myeong; Kim, Da Jeong; Woo, Soo Kyun; Lee, Jun-Young; Cho, Seong-Jin (Frontiers in Aging Neuroscience, 2020)
Cognitive reserve (CR) is known to be associated with the neuropsychological profile in older adults with normal cognition. We investigated the association between the comprehensive CR and the detailed neuropsychological profile in the early stage of cognitive decline. Fifty-six participants with mild cognitive impairment or subjective cognitive decline completed the cognitive reserve index questionnaire (CRIq) that yielded total, education, working activity, and leisure time scores (CRI-Total, CRI-Edu, CRI-WA, and CRI-LT, respectively). Mini-mental state examination (MMSE) and detailed neuropsychological evaluation were performed, and psychiatric symptom scales were administered, such as the geriatric depression scale, apathy evaluation scale (AES), positive and negative affect schedule (PANAS), and quality of life-Alzheimer’s disease. Correlation and linear regression analyses of the variables were performed. Path analysis was performed to find the effect of CR-Edu, CRI-WA, and CRI-LT on the composite cognitive score. The CRI-Total score was associated with the MMSE (B=0.01, p<0.001), PANAS-positive affect (B=0.19, p=0.049), and AES (B=0.30, p=0.018) scores. While the CRI-Edu score was associated only with the MMSE score (B=0.22, p=0.002) and the CRI-WA score was not associated with any of the variables, the CRI-LT score was associated with the MMSE score (B=0.074, p<0.001), naming ability (B=5.30, p=0.008), and phonemic fluency (B=4.21, p=0.009). Path analysis also indicated the direct effect of CRI-LT on the composite cognitive score (β=0.31, p=0.013). We found that the comprehensive CR was associated with global cognition, apathy, and positive affect in older adults at the pre-dementia stage. Additionally, only leisure activity was found to be associated with the detailed neuropsychological profile, such as naming ability and executive function. These results may imply the positive effect of leisure activity on cognition and psychiatric symptoms at the beginning of cognitive decline.